STUDENT SELF-GOVERNMENT AS AN IMPORTANT CONDITION FOR DEMOCRATIZATION OF HIGHER EDUCATION - Трибулькевич, К. Г. (Pedagogy of Higher and Secondary Education, 2011)
The state of study of problem of becoming and development of student self-goverment is considered on territory of the Ukrainian state, contradictions of this phenomenon are certain.